Devide Et Impera: Kebijakan Politik Belanda Dalam Memecah Persatuan di Nusantara - Karina Karina; Oktavia Sitorus; Salsalina Gurusinga; Rosmaida Sinaga (CV. Rayyan Dwi Bharata, 2024)
Devide et impera (bahasa Latin untuk